Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c9ra01048c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrogen peroxide co-precipitation and inert N2 atmosphere calcination on CeZrLaNd mixed oxides and the catalytic performance used on Pd supported three-way catalysts

Abstract: Hydrogen peroxide oxidation improves the grains growth. Inert N2 atmosphere calcination reduces the particle size and enlarges the pore channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This method can increase particle dispersion, resulting in smaller and softer crystal grain, and enriches pore channel, so particles will find it easier to chemically bond with coating agents. 28 In addition, in regard to the functioning of AMPTS, a study conducted by Khosroshahi et al, 24 carried out sonication of the Fe3O4 particles before they were functional with AMPTS. Sonication allows big particles to break down into smaller fragments, or particles that are uniform in size in the solution, so Fe3O4 particles will find it easier to chemically bond with AMPTS.…”
Section: Discussionmentioning
confidence: 99%
“…This method can increase particle dispersion, resulting in smaller and softer crystal grain, and enriches pore channel, so particles will find it easier to chemically bond with coating agents. 28 In addition, in regard to the functioning of AMPTS, a study conducted by Khosroshahi et al, 24 carried out sonication of the Fe3O4 particles before they were functional with AMPTS. Sonication allows big particles to break down into smaller fragments, or particles that are uniform in size in the solution, so Fe3O4 particles will find it easier to chemically bond with AMPTS.…”
Section: Discussionmentioning
confidence: 99%
“…The dispersion of cobalt and manganese particles could be promoted by the addition of hydrogen peroxide during the catalyst preparation and enhances crystal grain growth. Cui et al [49] and Liu et al [42] also reported that the addition of H 2 O 2 could promote the dispersion of metal particles and improve the crystal grain growth, and this consequently resulted in the formation of mixed oxides with good thermal stability.…”
Section: ]mentioning
confidence: 99%